Macroeconomic Determinants of Unemployment in ASEAN Countries: Implications for Education and SDGs - Chameliya Anggrahini; Yuni Prihadi Utomo (Universitas Negeri Semarang, 2026)
Unemployment remains a persistent challenge for many ASEAN countries and reflects not only economic instability but also the effectiveness of education systems in preparing a productive workforce. Macroeconomic conditions such as economic growth, inflation, foreign investment, and exchange rate fluctuations may influence labor market outcomes and the absorption of human resources. This study aims to analyze the effects of macroeconomic variables on unemployment in ASEAN countries and to examine their implications for education and sustainable development. The study employs panel data regression analysis using secondary data from eleven ASEAN countries during the 2021–2023 period obtained from the World Bank database. Model estimation was conducted using the Pooled Least Square, Fixed Effect Model, and Random Effect Model approaches, followed by model selection tests. The findings indicate that inflation and exchange rates significantly affect unemployment, while economic growth and foreign direct investment do not show a significant influence. These results suggest that macroeconomic stability plays an important role in shaping employment opportunities and workforce outcomes in the ASEAN region. The study contributes empirical evidence linking macroeconomic dynamics with labor market conditions and provides insights for education and employment policies aligned with the Sustainable Development Goals.